A Pragmatic Analysis of Deixis and Reference on Kim Hanbin Songs - Parjolo Aritonang; Claurin Sahusilawane (MATAI: International Journal of Language Education, 2022)
This pragmatic study aims to examine the different types of deixis from Cruse’s theory and references using pragmatic analysis in Lost at sea and Got it like that songs using descriptive qualitative. The result found from the analysis is that both songs use all five types of deixis. The personal deictic words occ. Thehe first person mainly refers to the singer or the songwriter. The second person refers to the addressee that is remarked by “you and your” and the last is third person “it” refers to something or someone that becomes the main thing or character in songs. Furthermore, the use of spatial deixis is quite a lot for both songs. Next, the temporal deixis that appeared in both songs is similar. Temporal deixis has two types of deixis, in “Lost at sea” and “Got it like that,” the pure deictic and verb tense occurred. The last, the social and discourse deixis with different deictic words, also occurred in both songs. Hopefully, the result could be a reference for students in the Linguistic Field in analyzing the written discourse with a Pragmatic Approach.